Requirements to the electrical discharge system used in the plasma-wave system - Korytchenko, K. V.; Dovbnya, A. N.; Volkolupov, Yu. Ya.; Tur, Yu. D.; Shkirida, S. M.; Yanchik, A. G. (Національний науковий центр "Харківський фізико-технічний інститут", 2004)
The electrical circuit creating a pulse arc is analyzed. The requirements to the elements of an electrical circuit in the electrical discharge circuit applied in the plasma-wave system are considered [1]. For analysis a discharge gap as a loading in the similar circuits is offered. The experience of practical realization of the circuit under consideration is given. Dynamics of an energy release in the channel of a pulse arc being characteristic for the chosen discharge circuit is experimentally established.

Проведено аналіз електричного кола газового розряду. Для аналізу запропоновано розглядати газорозрядний проміжок у виді навантаження у відповідному колі. Приведено дані з практичної реалізації такої системи електричного розряду. Динаміка енергетичного балансу в каналі газорозрядного проміжку, що характеризується обраним розрядним колом, підтверджена експериментально.
Вимоги до системи електричного розряду у плазмово-хвильовій системі